Human FSH Glycoform α-Subunit Asparagine52 Glycans: Major Glycan Structural Consistency, Minor Glycan Variation in Abundance - Butnev, Viktor Y.; May, Jeffrey V.; Brown, Alan R.; Sharma, Tarak; Butnev, Vladimir Y.; White, William K.; Harvey, David J.; Bousfield, George R. (Frontiers in Endocrinology, 2022)
Follicle-stimulating hormone consists of functionally significant variants resulting from the presence or absence of either one of two FSH subunit N-glycans. The two most abundant variants are fully-glycosylated FSH24 and hypo-glycosylated FSH21 (lacks Asn24 glycans). Due to its ability to bind more rapidly to the FSH receptor and occupy more FSH binding sites than FSH24, hypo-glycosylated FSH21 exhibits greater biological activity. Endoglycosidase F-1-deglycosylated FSH bound to the complete extracellular domain of the FSH receptor crystallized as a trimeric complex. It was noted that a single biantennary glycan attached to FSH Asn52 might preemptively fill the central pocket and prevent the other two FSH ligands from binding the remaining ligand-binding sites. As the most active FSH21 preparations possessed more rapidly migrating -subunit bands in Western blots, we hypothesized that Asn52 glycans in these preparations were small enough to enable greater FSH21 receptor occupancy in the putative FSHR trimer model. Highly purified hFSH oligosaccharides derived from each FSH subunit, were characterized by electrospray ionization-ion mobility-collision-induced dissociation (ESI-IM-CID) mass spectrometry. FSH glycans typically possessed core-linked fucose and were roughly one third bi-antennary, one third tri-antennary and one third tetra-antennary. FSH oligosaccharides largely lacked core fucose and were bi- or tri-antennary. Those Asn52 glycans exhibiting tetra-antennary glycan m/z values were found to be tri-antennary, with lactosamine repeats accounting for the additional mass. Selective Asn52 deglycosylation of representative pituitary hFSH glycoform Superdex 75 gel filtration fractions followed by ESI-IM-CID mass spectrometry revealed tri-antennary glycans predominated even in the lowest molecular weight FSH glycoforms. Accordingly, the differences in binding capacity of the same receptor preparation to different FSH glycoforms are likely the organization of the FSH receptor in cell membranes, rather than the Asn52 oligosaccharide.